Moderasi Beragama Untuk Persatuan Dan Kesatuan Bangsa Indonesia - Rafita; Fitra Aryansyah; Darul Fadhli (AL-Ikhtiar : Jurnal Studi Islam, 2024)
This article discusses the concept of religious moderation in Indonesia as a crucial element in strengthening national unity and cohesion. Through in-depth analysis of various strategies and implementations of religious moderation, the article reveals the complexity and urgency of the need for moderation in the context of religious diversity in Indonesia. By addressing the root causes of religious conflicts, this research highlights the importance of dialogue, tolerance, and appreciation of belief differences as the fundamental basis for building harmony and social solidarity. Emphasizing the active role of the community in strengthening religious moderation, the article also offers a progressive view on collective efforts to create an inclusive and just society. As a contribution to a broader understanding of religious moderation, this article is expected to serve as a valuable for the sustainability of peace and unity amidst religious diversity in Indone Indonesia the context of globalization and the challenges of modern times, religious moderation becomes increasingly relevant in strengthening national identity and preserving diversity as a cultural asset. This article underscores the crucial role of education in instilling the values of religious moderation from an early age, as well as the need for cross-sector cooperation to create a supportive environment for practicing moderation. By inspiring a spirit of mutual cooperation and respect, religious moderation is expected to become a key pillar in building a peaceful, fair, and prosperous society. Thus, this article calls on all elements of society to unite in the spirit of religious moderation to realize the vision of unity and cohesion of the Indonesian nation based on the values of diversity and harmony. Abstrak Artikel ini membahas konsep moderasi beragama di Indonesia sebagai elemen penting dalam memperkuat persatuan dan kesatuan nasional. Melalui analisis mendalam terhadap berbagai strategi dan implementasi moderasi beragama, artikel ini mengungkapkan kompleksitas serta urgensi perlunya moderasi dalam konteks keberagaman agama di Indonesia. Dengan menggali akar permasalahan yang melatarbelakangi konflik agama, penelitian ini menyoroti pentingnya dialog, toleransi, dan penghargaan terhadap perbedaan keyakinan sebagai landasan utama dalam membangun harmoni dan solidaritas sosial. Dengan menekankan peran aktif masyarakat dalam memperkuat moderasi beragama, artikel ini juga menawarkan pandangan progresif terhadap upaya bersama dalam menciptakan masyarakat yang inklusif dan berkeadilan. Sebagai kontribusi terhadap pemahaman yang lebih luas tentang moderasi beragama, artikel ini diharapkan dapat menjadi panduan yang berharga bagi keberlanjutan perdamaian dan persatuan dalam keragaman agama di Indonesia. Dalam konteks globalisasi dan tantangan zaman modern, moderasi beragama menjadi semakin relevan dalam memperkuat identitas bangsa dan menjaga keberagaman sebagai kekayaan budaya. Artikel ini menyoroti peran penting pendidikan dalam menanamkan nilai moderasi beragama sejak dini, serta perlunya kerjasama lintas sektor untuk menciptakan lingkungan yang mendukung bagi praktik moderasi. Dengan mengilhami semangat gotong-royong dan saling menghormati, moderasi beragama diharapkan dapat menjadi pilar utama dalam membangun masyarakat yang damai, adil, dan sejahtera. Dengan demikian, artikel ini mengajak seluruh elemen masyarakat untuk bersatu dalam semangat moderasi beragama demi mewujudkan visi persatuan dan kesatuan bangsa Indonesia yang berlandaskan pada nilai-nilai keberagaman dan harmoni.